Reliability and validity evaluation of the stigma of loneliness scale in Chinese college students - Zhiguang Fan; Xiaoli Shi; Shuhan Yang; Yueliang Sun; Ri Chen (BMC, 2024)
Abstract Background The stigma of loneliness exacerbates the negative effect of loneliness, reduces the willingness to seek help, damages interpersonal relationships, and threatens health status. However, there is currently no valid scale for measuring the stigma of loneliness in China. The study aims to translate the Stigma of Loneliness Scale (SLS) and evaluate the reliability and validity of the Chinese version. Methods The investigation was conducted in two phases. In the first phase, the SLS was used to conduct a questionnaire survey on 657 college students aged 17 to 24; in the second phase, the SLS, the UCLA Loneliness Scale (ULS-8), the Distress Disclosure Index (DDI), the Revised Cheek and Buss Shyness Scale (RCBS), the Self-Concealment Scale (SCS), the Social Interaction Anxiety Scale (SIAS), the Social Phobia Scale (SPS), the Kessler Psychological Distress Scale (K10), and the Rosenberg Self-Esteem Scale (RSES) were used to conduct the questionnaire survey on 801 college and graduates students aged 18 to 39. Results Two dimensions of Self-stigma of Loneliness and Public Stigma of Loneliness were extracted with a cumulative factor interpretation rate of 74.60% when conducting exploratory factor analysis on the first-stage data. The factor loading of each item ranged from 0.585 to 0.890, and the commonality ranged from 0.609 to 0.735. The confirmatory factor analysis and reliability and validity test were carried out on the data gathered in the second phase, indicating that the two-factor model fits well. In addition, the scores of SLS and all dimensions were significantly positively correlated with the total scores of ULS-8, RCBS, SCS, SIAS, SPS, and K10, and negatively correlated with those of DDI and RSES. The Cronbach's alpha coefficients for SLS and SSL and PSL dimensions were 0.957, 0.941, and 0.955. The cross-group invariance test found that the SLS was equivalent for males and females. Meanwhile, males scored significantly higher than females on both the total scores of SLS score and each dimension. Conclusions The Chinese version of SLS displayed satisfactory psychometric properties and can be a valid tool to assess the stigma of loneliness among Chinese young people.